Sauvegarder ou encourager la dentelle française ? - Emmanuel Pénicaut (In Situ)
The conservatory workshops for lace making at Le Puy-en-Velay (Haute-Loire) and Alençon (Orne) were founded in July 1976 at the initiative of President Valéry Giscard d’Estaing. They were placed under the authority of the ‘Mobilier national’, the national agency in charge of furniture and tapestry. In the two towns concerned, the conservatories replaced the last remaining private centres for training in lace making. Within the framework of an ambitious plan for supporting ‘métiers d’art’, arts and crafts activities, initiated by Pierre Dehaye (1921-2008), the original idea of setting up publicly owned and run workshops aimed, firstly, at preserving the traditional techniques of hand lace making, which were then on the point of disappearing, and, secondly, at encouraging economic initiatives in the lace market. This second ambition, associated with the Puy-en-Velay workshop in particular, did not meet with the success hoped for: hand made lace, as a lucrative economic activity, cannot stand up to the competition of mechanically made lace. Nonetheless, nearly fifty years after their foundation, the two workshops are still in activity and have carried out the first part of their mission with success. By the progressive renewal of models and of projects, they assure the perpetuation of the techniques of needle-point lace (at Alençon) and bobbin lace (at Le Puy-en-Velay) and have allowed leading contemporary artists to appropriate these techniques.